Case report: uveal melanoma with gastric metastases - Blasco, Carmelo (2025)
Uveal melanoma is the most common ocular cancer in adults, originating from melanocytes in the uvea. Although rare, its high metastatic potential, primarily to the liver, poses a significant challenge to patient prognosis. Gastric metastasis, though infrequent, may indicate advanced disease, with an incidence of up to 60% in post-mortem studies. We present the case of a 47-year-old patient with a history of uveal melanoma who developed gastric and hepatic metastases, as well as brain lesions, ultimately leading to her death within a short period.